MAPPING CONTEMPORARY ISLAMIC LEGAL THOUGHT IN INDONESIA: A DIALOG BETWEEN FIQH AND THE CULTURE OF THE ARCHIPELAGO - Zulfa, Firda Arina; Achmad, Mukhsin; Soylu, Davud; Fadhil (Universitas Islam Indonesia, 2025)
Purpose - This research examines the dynamics of Islamic legal thought in contemporary Indonesia concerning the cultural wisdom of the archipelago. This research aims to understand how sociopolitical changes, modernization of the Islamic education system, and awareness of local identity affect the acculturation process of Islamic law with local cultural values.Methods - This research uses historical-anthropological and socio-juridical approaches with qualitative methods. Data collection techniques included literature studies, historical document analysis, and in-depth interviews with 15 contemporary Islamic law thinkers in Indonesia.Findings - The results showed that Islamic fiqh in Indonesia underwent a process of adaptation through dialog with the local culture. Concrete examples of this acculturation include (1) inheritance division practices that accommodate customary law, such as the gono-gini system in Javanese society; (2) marriage rituals that combine elements of sharia with local traditions; and (3) the implementation of zakat, which is adjusted to the traditional economic system, including zakat on agricultural products that vary according to regional customs.Contribution/Limitations - Theoretically, this research enriches the study of Islamic law by highlighting the role of 'urf (custom) as a secondary source of law. This research provides input for formulating fatwas and Islamic law legislation responsive to the Indonesian sociocultural context. The limitation of this study lies in the scope of the area, which is still limited to specific case studies.Originality/Value - This research contributes to understanding how Islamic law can be contextualized in a multicultural society. It also opens up space for further exploration of the role of fatwa institutions and legal policies in responding to social dynamics in Indonesia.